Retroperitoneal invasive fibromatosis after laparoscopic radical resection of colon cancer: a case report and literature review - Shan, Tiantian; Zhang, Yiqi; Yao, Yang; Li, Min; Li, Xiaoying (Frontiers in Oncology, 2025)
Invasive fibromatosis is a rare, locally invasive, benign fibrous tumor that mainly occurs in the anterior abdominal wall and limbs, with a lower incidence in the retroperitoneum. This article reports a case of retroperitoneal invasive fibromatosis in a 63-year-old male patient. The patient underwent resection for sigmoid colon cancer and was diagnosed with retroperitoneal invasive fibromatosis through enhanced CT, pathological examination and Whole Exome Sequencing one year after surgery. Given the rarity of postoperative surgery-related retroperitoneal invasive fibromatosis in patients with colorectal cancer, this article aims to provide a reference for clinical research on retroperitoneal invasive fibromatosis by reporting this case.